A Perspective of Environmental and Geographic Engineering from the Scholarly Production of the Undergraduate Program (2021)
Producing new knowledge in emerging disciplines that combine various domains is a task that has a long way to go, mainly the integrations between environmental and geographic issues to which some experienced researchers have made significant contributions. This article examines the works of young people in the Latin American engineering context who have begun to share their ideas with the world. The objective is to establish a perspective of environmental and geographic engineering from the scholarly production promoted by the undergraduate program. The method comprises four stages that start with exploring and compiling 91 visible scholarly products between 2005–2019 for subsequent categorization. We then perform a general quantitative analysis of the contents and supplement the perspective with a synthetic interview with experts. As a result, we classify the scholarly production into five categories and thirteen subcategories. We also carry out a spatial analysis of such production, noting a constructive process of successive contributions. This exploration traces new paths, examines the possibility of joining efforts, and, above all, introduces new generations to the dialogue of knowledge and interdisciplinarity.